2007
DOI: 10.1007/s10803-006-0341-5
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Young Siblings of Children with Autism from 4 to 54 Months

Abstract: Cognitive and language skills of 39 siblings of children with autism (SIBS-A) and 39 siblings of typically developing children (SIBS-TD) at ages 4, 14, 24, 36, and 54 months were compared. Twelve of the 39 SIBS-A revealed a delay in cognition and/or language (including one child diagnosed with autism) compared to only two SIBS-TD. Developmental trajectories revealed that the cognitive differences disappeared by age 54 months, but some differences in language ability remained. Thus, most SIBS-A were well-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 39 publications
7
81
0
7
Order By: Relevance
“…As Pickles and Angold (2003) state, in order to understand the relationships between psychopathology, its aetiology, outcome and other factors, "we need to adopt a truly empirical approach that is unblinkered by either categorical or dimensional prejudices" (p548). Retrospective studies of early predictors of psychopathology are limited by issues of recall bias while prospective cohorts of subjects at 'high risk' (Besag, 2006;Cassell et al, 2007;Gamliel, Yirmiya, & Sigman, 2007;Iverson & Wozniak, 2007;Landa, Garrett-Mayer, Landa, & Garrett-Mayer, 2006;Loh et al, 2007;Merin, Young, Ozonoff, & Rogers, 2007;Toth, Dawson, Meltzoff, Greenson, & Fein, 2007;Yirmiya et al, 2006;Zwaigenbaum et al, 2005b;Yirmiya et al, 2007;Zwaigenbaum et al, 2005a;Zwaigenbaum et al, 2005a) may reveal early indicators of neurodevelopmental disorders, such as autism, but are subject to a variety of forms of selection and ascertainment bias. For example, prospective studies of children exposed to smoking in pregnancy and of children with very low birth weights have shown increased rates of ADHD and of ADHD/autism symptoms (Hultman et al, 2007;Indredavik, Brubakk, Romundstad, & Vik, 2007), but to what extent such factors alone can contribute to these difficulties can best be determined in the context of general population birth cohort studies.…”
Section: Problems With Existing Studies Of Early Neurodevelopment Andmentioning
confidence: 99%
“…As Pickles and Angold (2003) state, in order to understand the relationships between psychopathology, its aetiology, outcome and other factors, "we need to adopt a truly empirical approach that is unblinkered by either categorical or dimensional prejudices" (p548). Retrospective studies of early predictors of psychopathology are limited by issues of recall bias while prospective cohorts of subjects at 'high risk' (Besag, 2006;Cassell et al, 2007;Gamliel, Yirmiya, & Sigman, 2007;Iverson & Wozniak, 2007;Landa, Garrett-Mayer, Landa, & Garrett-Mayer, 2006;Loh et al, 2007;Merin, Young, Ozonoff, & Rogers, 2007;Toth, Dawson, Meltzoff, Greenson, & Fein, 2007;Yirmiya et al, 2006;Zwaigenbaum et al, 2005b;Yirmiya et al, 2007;Zwaigenbaum et al, 2005a;Zwaigenbaum et al, 2005a) may reveal early indicators of neurodevelopmental disorders, such as autism, but are subject to a variety of forms of selection and ascertainment bias. For example, prospective studies of children exposed to smoking in pregnancy and of children with very low birth weights have shown increased rates of ADHD and of ADHD/autism symptoms (Hultman et al, 2007;Indredavik, Brubakk, Romundstad, & Vik, 2007), but to what extent such factors alone can contribute to these difficulties can best be determined in the context of general population birth cohort studies.…”
Section: Problems With Existing Studies Of Early Neurodevelopment Andmentioning
confidence: 99%
“…Only one group to date has reported on the developmental outcome of Sibs-ASD beyond four years of age. Gamliel et al (2007Gamliel et al ( , 2009 reported that by approximately 54 months of age, early differences in cognitive abilities were no longer present for Sibs-ASD (Gamliel et al 2007). However, at seven years of age, differences were noted between sibling groups with increased numbers of Sibs-ASD exhibiting cognitive, language, or academic difficulties relative to Sibs-TD (Gamliel et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a los H-TEA, otros trabajos apuntan que aquellos que serán después diagnosticados, pueden llegar a tener retrasos en el lenguaje y en la producción de gestos observables también durante el primer año de vida (Mitchell et al, 2006;Ozonoff et al, 2010;Rozga et al, 2011), con una menor producción de gestos de hasta del 50%, en comparación con los niños con bajo riesgo o con los niños de riesgo que no llegan a desarrollar el trastorno (Talbott, Nelson & Tager-Flusberg, 2015). En el caso de los H-TEA que no son diagnosticados, aunque también pueden tener dificultades en gestualidad y lenguaje, éstas no se llegan a manifestar hasta los dos años de vida (Gamliel, Yirmiya, Jaffe, Manor & Sigman, 2009;Gamliel, Yirmiya & Sigman, 2007;Iverson & Wozniak, 2007;Mitchell et al, 2006;Yirmiya et al, 2006). Estas conclusiones ponen de manifiesto la relación entre gestualidad y lenguaje en niños con riesgo de TEA, especialmente la relación entre señalar con el dedo y el desarrollo del lenguaje en este grupo de población infantil (LeBarton & Iverson, 2016) …”
Section: Gestualidadunclassified